1999
DOI: 10.1038/sj.bmt.1701916
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous cord blood transplantation of ex vivo expanded together with non-expanded cells for high risk leukemia

Abstract: Summary:In the absence of a donor alternative a stem cell transplantation consisting of two cord blood components originating from the haploidentical brother was performed in a 2-year-old girl with c-ALL, early CNS relapse and 7% of blast cells in the BM 14 days before transplantation. Because of various ongoing infectious complications at that time, 1/8 of the immunogenetically acceptable sibling cord blood was ex vivo expanded 10 days before the transplantation date. The total CB consisting of 1.17 ؋ 10 9 NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 19 publications
(12 reference statements)
1
46
1
4
Order By: Relevance
“…26,30,44,45 Another potential approach to reduce TRM in UD-UCBT is to reduce the time of engraftment by using ex vivo expanded cord blood units. 24,46,47,48 However, some concerns have Leukemia been expressed because of the possible negative impact of these methods on long-term engraftment. 49,50 The combination of expanded and unmanipulated fractions of UCB graft could provide rapid short-and long-term engraftment.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…26,30,44,45 Another potential approach to reduce TRM in UD-UCBT is to reduce the time of engraftment by using ex vivo expanded cord blood units. 24,46,47,48 However, some concerns have Leukemia been expressed because of the possible negative impact of these methods on long-term engraftment. 49,50 The combination of expanded and unmanipulated fractions of UCB graft could provide rapid short-and long-term engraftment.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…Attempts to increase UCB cell dose has laid the basis for laboratory 56 and phase I clinical trials [57][58][59] focused on ex vivo expansion of UCB grafts. Although early clinical trials reported thus far do not point to more rapid hematopoietic recovery in UCB recipients, there is improved day 100 survival compared with historical controls.…”
Section: Future Initiatives: Ucb Transplantationmentioning
confidence: 99%
“…Completion of ongoing studies is needed to determine if similar improvements in outcome will be observed in future patients with CML, and at even lower UCB doses. Moreover, through identification of the hematopoietic and/or accessory cells that facilitate engraftment and by optimization of the infusion sequence of expanded and unexpanded cells as reported elsewhere, 10 it may be possible to develop better expansion strategies that translate into a more consistent improvement in outcomes for unrelated UCB recipients.…”
Section: Resultsmentioning
confidence: 99%